Inflammatory rheumatic diseases with onset after SARS-CoV-2 infection or COVID-19 vaccination: a report of 267 cases from the COVID-19 and ASD group - Laura Massaro; Annamaria Iagnocco; Florenzo Iannone; Corrado Campochiaro; Maria De Santis; Ilaria Cavazzana; Piero Ruscitti; Roberto Giacomelli; Rosario Foti; Lorenzo Dagna; Giovanna Cuomo; Giacomo De Luca; et al. (RMD Open)
Objectives To better define the spectrum of new-onset post-COVID-19 and post-COVID-19 vaccine inflammatory rheumatic diseases (IRD) from a large multicentric observational study.Methods Consecutive cases of IRD encountered during a 12-month period and satisfying one of the following inclusion criteria: (a) onset of the rheumatic manifestations within 4 weeks from SARS-CoV-2 infection or (b) onset of the rheumatic manifestations within 4 weeks from the administration of one of the COVID-19 vaccines ws recruited.Results The final analysis cohort comprised 267 patients, of which 122 (45.2%) in the post-COVID-19 and 145 (54.8%) in the postvaccine cohort. Distribution of IRD categories differed between the two cohorts: the post-COVID-19 cohort had a higher percentage of patients classified as having inflammatory joint diseases (IJD, 52.5% vs 37.2%, p=0.013) while the post-vaccine cohort had a higher prevalence of patients classified as polymyalgia rheumatica (PMR, 33.1% vs 21.3%, p=0.032). No differences were detected in the percentage of patients diagnosed with connective tissue diseases (CTD 19.7% vs 20.7%, p=0.837) or vasculitis (6.6% vs 9.0%, p=0.467). Despite the short follow-up period, IJD and PMR patients’ response to first-line therapy was favourable, with both groups achieving a drop in baseline disease activity scores of ~30% and ~70% respectively.Conclusion Our article reports the largest cohort published to date of new-onset IRD following SARS-CoV-2 infection or COVID-19 vaccines. Although causality cannot be ascertained, the spectrum of possible clinical manifestations is broad and includes IJD, PMR, CTD and vasculitis.